Entomophagous and entomopathogenic fungi effectiveness of Gynaikothrips uzeli (Thysanoptera: Phlaeothripidae) on Ficus benjamina (Moraceae) - Cambero-Campos, Angel Jhonathan; Carvajal-Cazola, Carlos; Ulloa-Rubio, Karla; Ríos-Velasco Claudio; Berlanga-Reyes, David; Robles-Bermúdez Agustín; Santillán-Ortega Candelario (Revista Mexicana de Ciencias Agrícolas, 2018)
The presence of thrips, Androthrips ramachandrai Karny and the anthocorid Montandoniola confusa Streito & Matocq, predators of the phytophagous thrips Gynaikothrips uzeli Zimmerman is reported in Ficus benjamina galls, commonly named “Benjamina” in San Blas, Santiago Ixcuintla and Tepic, Nayarit, Mexico. The biological activity of Beauveria bassiana was evaluated (isolates Bb-S1, S2 and Bb-S3), Metarhizium anisopliae (Ma-A and Ma-C), and Paecilomyces fumosoroseus (Pf-4a) as biological control agents for Gynaikothrips uzeli under laboratory conditions. The isolates Bb-S1 and Ma-A caused the highest mortality in larvae (40.05 ± 5.08, 64.8 ± 3.01) and adults (54.3 ± 7.8, 60.5 ± 6.4) respectively.